Mycotoxins in Plant-Based Dietary Supplements: Hidden Health Risk for Consumers - Veprikova, Zdenka; Zachariasova, Milena; Dzuman, Zbynek; Zachariasova, Alena; Fenclova, Marie; Slavikova, Petra; Vaclavikova, Marta; Mastovska, Katerina; Hengst, Daniel; Hajslova, Jana (Journal of agricultural and food chemistry, 2015)
Mycotoxin contamination of dietary supplements represents a possible risk for human health, especially in the case of products intended for people suffering from certain health conditions. The aim of this study was to assess the extent of this problem based on analyses of a wide set of herbal-based dietary supplements intended for various purposes: (i) treatment of liver diseases (milk thistle); (ii) reduction of menopause effects (red clover, flax seed, and soy); and (iii) preparations for general health support (green barley, nettle, goji berries, yucca, etc.) The analytical method including 57 mycotoxins was based on a QuEChERS-like (quick, easy, cheap, effective, rugged, safe) approach and ultrahigh performance liquid chromatography coupled with tandem mass spectrometry. The main mycotoxins determined were Fusarium trichothecenes, zearalenone and enniatins, and Alternaria mycotoxins. Co-occurrence of enniatins, HT-2/T-2 toxins, and Alternaria toxins was observed in many cases. The highest mycotoxin concentrations were found in milk thistle-based supplements (up to 37 mg/kg in the sum).
Keywords: Mycotoxins; depsipeptidy; Food Contamination; Tandem Mass Spectrometry; Dietary Supplements; Zearalenone; vysokoúčinná kapalinová chromatografie; lidé; zearalenon; potravní doplňky; mykotoxiny; Risk Factors; Plant Preparations; kontaminace potravin; Chromatography, High Pressure Liquid; Trichothecenes; tandemová hmotnostní spektrometrie; rizikové faktory; trichotheceny; rostlinné přípravky; Depsipeptides; Humans